Integrating SWOT, STP, and 7Ps Frameworks to Strengthen MSME Competitiveness: A Case Study of Bi Omeh Grilled Chicken in Indonesia - Wulandani, Yolanda Seva; Masruri, Masruri (PERFECT EDUCATION FAIRY, 2026)
This study examines the marketing strategies employed by Bi Omeh Grilled Chicken, a micro, small, and medium enterprise (MSME) in Tangerang Regency, Indonesia. Using a qualitative case study approach, data were collected through interviews, observation, and documentation, and analyzed with NVivo software to facilitate coding and visualization. The research applies SWOT, STP, and the 7Ps marketing mix to evaluate the firm’s strategic positioning. Findings show that Bi Omeh Grilled Chicken demonstrates strengths in taste quality, affordable pricing, and strategic location, while weaknesses include limited digital promotion and slow service delivery. This study highlights the importance of integrated marketing strategies for MSMEs to remain competitive in a highly dynamic food and beverage industry.